Yogurt consumption is associated with a better lifestyle in Brazilian population - Possa, Gabriela; Corrente, José Eduardo [UNESP]; Fisberg, Mauro (Springer Nature, 2017)
Background: The importance of dairy products is recognized for their health benefits. However, additional investigation is required to understand the characteristics of the lifestyle of people who incorporate yogurt into their eating routine. Then, the aim of this study was to compare the lifestyle of yogurt consumers and non-consumers. Methods: A total of 2610 individuals between the ages of 18 and 59 years were recruited and selected for the study, having as the primary criterion the report of frequency of yogurt consumption. Two study groups were formed: consumers (frequency of yogurt consumption ≥ four times a week during the last year) and non-consumers (consumption frequency of less than once a week), paired for age, sex, and socioeconomic class. A structured questionnaire was applied to obtain the data regarding anthropometric characteristics (weight, height, and waist circumference), lifestyle (food consumption, physical activity, smoking, and alcohol consumption), socioeconomic information (relationship status, level of education, and work) and presence of morbidities. Based on the quantity of consumption in grams/day of yogurt and milk, cheeses, and fruit smoothies, four other analysis groups were formed: LOW-Y/LOW-D (low consumption of yogurt and other dairy products); LOW-Y/HIGH-D (low consumption of yogurt and high consumption of other dairy products); HIGH Y/LOW-D (high consumption of yogurt and low consumption of other dairy products); and HIGH-Y/HIGH-D (high consumption of yogurt and other dairy products). Chi-squared and Student's t tests were used to assess the relationships of these factors. Results: The yogurt consumers had a higher educational level (≥8 years: 83.8% vs. 79.9%), a higher frequency of individuals working and/or currently studying (67.7% vs. 65.5%), were more physically active at leisure time (17.2% vs. 14.3%), had reduced alcohol intake (3.6 g/day vs. 6.4 g/day) and a lower frequency of smoking (21.7% vs. 25.5%) compared to non-consumers (p < 0.05). Besides, individuals included in the Groups HIGH-Y/LOW-D and HIGH-Y/HIGH-D, when compared to those included in the Group LOW-Y/LOW-D, presented a significantly greater intake of calcium, vitamin D, phosphorus, and saturated fat. Conclusions: This research demonstrated an association between consumption of yogurt and a better lifestyle.
Keywords: Cross-sectional studies; Diet; Life style; Yogurt